Hubungan Penggunaan Game Edukasi Sebagai Media Evaluasi Pembelajaran PAI dan Motivasi Belajar Siswa Kelas 7 di SMPN 1 Kota Bogor - Maulidina, Azzahra; Indriya; Asep Gunawan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to determine whether there is a relationship between using educational games as a learning evaluation medium in Islamic Religious Education subjects and the learning motivation of grade 7 students at SMPN 1 Bogor. This research is quantitative research using a correlational type. The population in this study was class 7 students, totaling 309 students, with a sample of class 7-D and 7-H students totaling 78 students. The data collection technique in this research uses observation, questionnaires, and documentation. The information obtained from respondents through this questionnaire was used to find the relationship between using educational games as a medium for evaluating Islamic Education learning and learning motivation. This research uses a correlation test to determine the hypothesis. The hypothesis results obtained based on this correlation test are that the significance value of variable X and variable Y both show a value of 0.000 < 0.05 with a Pearson correlation value of 0.558. These results show that Ha is accepted and H0 is rejected, which means there is a positive relationship with a moderate correlation between using educational games as a learning evaluation medium and the learning motivation of grade 7 students at SMPN 1 Bogor.